Psychometric Properties of the Generalized Anxiety Disorder-7 and Generalized Anxiety Disorder-Mini in United States University Students - Byrd-Bredbenner, Carol; Eck, Kaitlyn; Quick, Virginia (Frontiers in Psychology, 2020)
Background: Generalized Anxiety Disorder (GAD) is common in young adults, yet few studies have established the psychometric properties of the GAD-7 screener in college students. Methods: A secondary analysis of 3 studies was conducted to determine GAD-7 factor structure stability, create a GAD-Mini version using standard procedures, evaluate the psychometric properties, validity, sensitivity, specificity, and predictive values of both versions in young adults. Results: Exploratory and confirmatory principal components analysis indicated the GAD-7 has a single factor structure with strong loadings, reliability, and stability across data collected at 3 studies. Data from all studies met criteria indicative of good to excellent model fit. Iterative confirmatory principal components analyses revealed the most parsimonious set of items that maintained scale unidimensionality, strong loadings, and high reliability was 2 items (not able to stop or control worrying and worried too much). Both the GAD-7 and GAD-Mini exhibited good construct and convergent validity. Specificity, sensitivity, and negative predictive value were high, and positive predictive value was moderate to high for the GAD-Mini. Conclusions: The GAD-Mini is a psychometrically sound tool that can serve as a step toward universal screening in clinical practice and contribute to early treatment and improved health outcomes for GAD.